1990
DOI: 10.1007/bf02245791
|View full text |Cite
|
Sign up to set email alerts
|

Regional neurotransmitter responses after acute and chronic electroconvulsive shock

Abstract: Regional neurotransmitter changes after acute and chronic electroconvulsive shock (ECS) were studied using the technique of repeated microdialysis. Microdialysis was carried out on alternate sides of the brains of anaesthetised rats before and during the first and the eighth ECS or sham (control) treatments. Extracellular fluid release of monoamines and their metabolites was measured in the frontal cortex, striatum and nucleus accumbens using HPLC with electrochemical detection. The first ECS produced selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 17 publications
2
23
1
Order By: Relevance
“…Glue et al (1990) reported a comparable increase in NA release in frontal cortex. This change in release was only seen after multiple ECS treatment suggesting a similarity with the requirements for therapeutic effectiveness in man.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Glue et al (1990) reported a comparable increase in NA release in frontal cortex. This change in release was only seen after multiple ECS treatment suggesting a similarity with the requirements for therapeutic effectiveness in man.…”
Section: Discussionmentioning
confidence: 80%
“…Two recent reports have used in vivo microdialysis to investigate the effects of acute and chronic ECS on the release of endogenous dopamine from the rat corpus striatum (Glue et al, 1990;Zis et al, 1991 (Thomas & Holman, 1991a,b Paxinos & Watson (1986). Body temperature was maintained at 37.5°C by use of a rectal probe and heating blanket.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of a single ECS, NE synthesis is stimulated in the LC and its terminal fields (14) and a rapid, shortlasting increase in TH enzyme activity is induced ( 15,16 increase in TH mRNA levels, a twofold increase in the LC measured 24 h after ECS, is much larger in magnitude and longer in duration than thiat produced by acute stress (5,17,18) or reserpine admninistration (19), treatments which stimulate NE…”
Section: Discussionmentioning
confidence: 99%
“…In various animal models it is reported that there is an acute elevation in the brain content of dopamine and with each ECS 11,12 ; there is also an increase in D 1 -receptor density in the region of rat brain 13 . This explains the above observations in our present study.…”
Section: Ecs Effect On Monoamine Mediated Responsesmentioning
confidence: 99%